Peranan Bank Syariah Dalam Meningkatkan Pendapatan Umkm Pada Pedagang Pasar Sibolga Nauli - Syarifah Isnaini; Rizki Pratiwi Harahap (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
This theory can be the basis or reference in conducting this research. This type of research is research conducted with descriptive qualitative methods. The data collection tools used were observation, interviews, and documentation, while data processing techniques and data analysis were carried out by means of qualitative case studies at Bank Syariah Indonesia KC Sibolga. The results of this study indicate that Islamic banks play a role in increasing MSME income, which can be seen from business development, increased income, increased sales volume, and the addition of new employees to their businesses after financing at BSI KC Sibolga bank. The role of the BSI KC Sibolga bank is by providing business capital financing, as well as facilitating and facilitating MSMEs in obtaining financing. Efforts made by Islamic banks in boosting MSME actors are by providing KUR type financing.